A novel κ-carrageenan extracting process with calcium hydroxide and carbon dioxide. (June 2022) - Liu, Yao; An, Ding; Xiao, Qiong; Chen, Fuquan; Zhang, Yonghui; Weng, Huifen; Xiao, Anfeng
Abstract: Traditional κ-carrageenan extraction method with alkaline (NaOH) has the problems of low yield, huge water consumption, and high sewage treatment cost. Thus, an efficient, water-saving, and eco-friendly κ-carrageenan extraction method was explored using Ca(OH)2 for boiling extract and CO2 for neutralization. The results showed that the quality of κ-carrageenan extracted by Ca(OH)2 (Ca-KC) was superior to that extracted by NaOH (Na-KC). The Fourier transform infrared spectroscopy result indicated that the absorption peak of Ca-KC at 1250 cm −1 weakened, whereas that at 931 cm −1 enhanced compared with those of the Na-KC. This result was consistent with the results of low sulfate content of Ca-KC and high content of 3, 6-anhydro-d -galactose. Thermogravimetric analysis and differential scanning calorimetry analysis indicated that Ca-KC had a better thermal stability than Na-KC. The average molecular weight and molecular weight distribution of Ca-KC were not significantly different from those of Na-KC. Moreover, the gel strength and whiteness of Ca-KC increased, whereas its viscosity and transparency all decreased compared with those of the Na-KC. The yield of Ca-KC (36.2% ± 0.8%) was 40% higher than that of Na-KC (25.8% ± 0.7%), while material consumption significantly decreased and wastewater was avoided. Considering the above advantages, this new extraction method for κ-carrageenan extraction is a promising alternative to the traditional NaOH extraction method. Graphical abstract: Image 1 Highlights: κ-carrageenan extraction using Ca(OH)2 presented eco-friendly and efficient merits. The quality of Ca-KC was superior to that of Na-KC. Ca-KC had the better desulfation effect and structural stability. Viscosity of Ca-KC decreased, while gel strength increased.